A psicanálise realizada em libras: demandas e desafios da clínica com pacientes surdos - Halabe, Dannilo Jorge Escorcio (2018)
The psychoanalytic service presupposes the interaction between the analyst and the patient through a channel of communication in which the method of association may come. Analyzing the cases in the literature of patients with total deafness, which use lip reading, the Brazilian Sign Language (LIBRAS) and speech to communicate, realize that analysts rely only on oral language to perform the service. Against this movement, this thesis demonstrates the importance of the analysis with the deaf be held in LIBRAS because sign language provides a better expression of their feelings, being more natural to them and behaving every expression of slang, metaphors and jokes, like the portuguese spoken. Field research analyzed interviews with deaf people, interpreters and analysts in São Luís - MA, in different places (schools, clinics, universities, etc.). They evaluated the cases seen by psychoanalysts of deaf patients, revealing the strategies and problems faced by analysts, comparing with the speech of deaf people about their culture, including the importance that is given to LIBRAS. This paper discusses the importance of the training of analysts in LIBRAS and their participation in the deaf culture for the accomplishment of the consultations. It also provides an understanding of LIBRAS as the mother tongue (L1) of the deaf at any time during the development of children, youth and adults